2021
DOI: 10.3390/microorganisms9122585
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bacterial Microbiota in Digestive Cancer Patients: A Systematic Review

Abstract: The relation between the gut microbiota and human health is increasingly recognized. Recently, some evidence suggested that dysbiosis of the oral microbiota may be involved in the development of digestive cancers. A systematic review was conducted according to the PRISMA guidelines to investigate the association between the oral microbiota and digestive cancers. Several databases including Medline, Scopus, and Embase were searched by three independent reviewers, without date restriction. Over a total of 1654 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 86 publications
(187 reference statements)
0
19
0
Order By: Relevance
“… 7 Notably, clinical observations have demonstrated that the prevalence of PC significantly increases in chronic periodontitis patients. 8 , 9 Porphyromonas gingivalis ( P. gingivalis ), a keystone oral-resident periodontal pathogen, was reported not only being involved in the oncogenesis of several gastrointestinal cancers, 10 such as esophageal cancer 11 and colorectal cancer, 7 but also being epidemically correlated with PC. 12–14 These observations suggest the potential causative link between periodontitis and PC might be mediated by P. gingivalis .…”
Section: Introductionmentioning
confidence: 99%
“… 7 Notably, clinical observations have demonstrated that the prevalence of PC significantly increases in chronic periodontitis patients. 8 , 9 Porphyromonas gingivalis ( P. gingivalis ), a keystone oral-resident periodontal pathogen, was reported not only being involved in the oncogenesis of several gastrointestinal cancers, 10 such as esophageal cancer 11 and colorectal cancer, 7 but also being epidemically correlated with PC. 12–14 These observations suggest the potential causative link between periodontitis and PC might be mediated by P. gingivalis .…”
Section: Introductionmentioning
confidence: 99%
“…Taking part in the digestion process, the intestinal microbiota synthetizes essential amino acids and vitamins. A symbiotic microbiota is normally characterized by a high diversity, and it can resist changes occurring during physiological stress, being able to stimulate the immune response [36]. Quality and amount of the intestinal microbiota could be modified by different factors such as diet, alcohol and smoking, impairing its ability to interface with the immune system and leading to an uncontrolled degree of inflammation [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics can also be added to these techniques, which tracks all metabolites produced by the microorganism involved in biological processes [ 9 , 10 , 11 ]. The human gastrointestinal tract, mouth, vagina, respiratory tract, and skin are colonized by microbial communities or microbiota [ 12 ].…”
Section: Introductionmentioning
confidence: 99%